USING AUTHENTIC TEXTS IN FOREIGN LANGUAGES CLASSSES - Дjumabaeva V.Т. (FAN va JAMIYAT, 2020)
The article proposes methods of using authentic materials in teaching foreign languages. Authentic learning tasks stimulate interaction with texts and based on the operations, that are performed white working with source information outside the classroom.